Comprehensive bioinformatic analysis of HTR7: A potential biomarker for diagnosis, survival, and immunotherapy in pan-cancer - Yuhao Yao; Xiao Xia; Lanxin Zhang; Hongtai Xiong; Size Li; Wei Hou (PLoS ONE, 2025)
We used several public databases to perform a comprehensive pan-cancer analysis to determine the potential role of HTR7 in diagnosing tumors, predicting prognosis, and predicting cancer immunotherapy response. The results showed that HTR7 is highly expressed in 12 tumors and lowly expressed in 13 tumors compared with normal tissues. HTR7 has a specific diagnostic value in 18 cancers, especially in COAD, HNSC, KIRC, PCPG, and READ. High expression of HTR7 was associated with a favorable prognosis in ACC, COAD, KIRC, KIRP, PRAD, READ, SKCM, and THCA, while in CESC, ESCA, GBM, HNSC, PAAD, and THYM, high expression of HTR7 was associated with an unfavorable prognosis. In most tumors, HTR7 expression was positively correlated with the infiltration of monocytes, macrophages, and myeloid dendritic cells and negatively correlated with Th1 infiltration. We found that HTR7 expression was positively correlated with CD274, CTLA-4, HAVCR2, PDCD1, PDCD1LG2, and TIGIT in numerous tumors. Furthermore, our study showed that aberrant methylation of HTR7 was associated with the infiltration of many immune cells, including Th1, Th17, DC, macrophages, etc. In cancer pathways, HTR7 could inhibit the cell cycle, DNA damage, and hormone AR pathways and activate the EMT and RAS/MAPK pathways. GO and KEGG enrichment analyses revealed that HTR7 could participate in the G protein-coupled receptor signaling pathway, serotonin receptor signaling pathway, hormone signaling, cAMP signaling pathway, etc. Several drugs, including 5-fluorouracil, gemcitabine, sunitinib, tipifarnib, and trametinib, may be sensitive to high HTR7 expression in tumors.